COMPARISON TWO LOCATIONS OF LIGHTNING DETECTION - Septiadi, Deni; Suntoko, Hadi; Widodo, Anton; Noor, Riza Arian (Jurnal Meteorologi Klimatologi dan Geofisika, 2018)
The objective of this study was to identify the lightning distribution by comparing of two lightning sensors located in Jakarta and Bandung. Using Storm Tracker Lightning Detector maintained by the Indonesia Agency for Meteorology, Climatology and Geophysics (BMKG), Cloud-to-Ground lightning (CG) analyzed with a various radius i.e. 0.1?, 0.5? and 1.0?. Storm Tracker Lightning Detector consists of an antenna connected to the PCI card and able to detect Low Frequency (LF) of radio signals generated by lightning (10 KHz to 200 KHz). The data used are based on the available records of near real time 15 minutes CG lightning data. This study aims at revealing ideally possible location of the lightning sensor to optimize lightning detection. For further analysis, the distribution of the CG lightning estimated in the target area located about the middle between Jakarta and Bandung. The analysis of lightning described by calculating the detection efficiency of lightning sensor and the analysis of lightning location error.